Quality Management Practices and Competitiveness of Manufacturing Firms in Nairobi - Muiruri, Jacqueline Wangui; Peterson, Dr. Magutu Obara (International Journal of Supply Chain and Logistics, 2020)
Purpose: The main objective of this study was to establish the influence of quality management practices on competitiveness of manufacturing firms in Nairobi. Methodology: The research adopted a descriptive survey research design in trying to focus on manufacturing firms operating in Nairobi. This study used the list of manufacturing firms in Nairobi as provided in the KAM directory that showed a total of 499 manufacturing firms operating in Nairobi. The research study used stratified random sampling. The sample size of the research study was 50 manufacturing firms. The data was collected by use of structured questionnaires. It was done from operations managers, quality assurance managers and supply chain managers or their equivalents since they were deemed to be well versed and had good understanding of strategic quality management practices and operational activities of manufacturing firms. The information from the analysis was presented by use of pie charts, graphs, bar charts and tables to search for any correlation between strategic quality management practices and firms' competitiveness. Results and conclusion: The results revealed that bench marking and competitiveness were positively and significantly correlated (r=0.578, p=0.000). The results further showed that continuous improvement and competitiveness were positively and significantly related (r=0.620, p=0.000). It was additionally verified that supplier partnering and competitiveness were positively and significantly related (r=0.510, p=0.000). Equally, the results showed that six sigma and competitiveness were positively and significantly related (r=0.529, p=0.000). Finally, the results revealed that quality management practices and competitiveness were positively and significantly related (r=0.642, p=0.000). The results indicated that the overall model was statistically significant. Further, the results imply that the independent variables are good predictors of firm competitiveness. This was reinforced by an F statistic of 21.769 and the reported p value (0.000) which was less than the conventional probability of 0.05 significance level. Policy recommendation: The author recommended that manufacturing firms should institute and involve the support of strategic leadership to monitor the adoption and implementation of quality management practices as a way of improving their competitiveness in their respective industries. Further, firms should come up with as many benchmarking approaches and to also hold several of them so as to increase on adoption of effective mechanism that makes firms more competitive